Mathematical model of energy conversion mechanism in screw centrifugal pump based on load criteria of blade airfoil. Issue 7 (2nd October 2017) - Quan, Hui; Fu, Baiheng; Li, Rennian; Li, Guangxian; Zhang, Zhengjie; Li, Jin
Abstract : Purpose: To analyze the work principle and capacity of energy conversion in each segment of profile lines, the energy transfer from impeller to transmission medium is separated into head coefficient and load coefficient to analyze the energy transfer process. The concepts of airfoil lift coefficient and drag coefficient are used; the third manifestation of the Euler equations is used as well. Design/methodology/approach: The numerical simulation of energy conversion mechanism based on load criteria of vane airfoil has been established in screw centrifugal pump to explain its energy conversion mechanism in an impeller. Upon this basis, the velocity and pressure along the entire blade are investigated through the numerical simulation of internal solid–liquid flow in the pump. The energy conversion process under load criteria in the blade airfoil has also been obtained. Findings: The research suggests that the mathematical model of energy conversion mechanism based on the load criteria of the vane airfoil is reliable in the screw centrifugal pump. The screw centrifugal blade has twice or even several times the wrap angle than the ordinary centrifugal blade. It is a large wrap angle that forms the unique flow channel which lays the foundation for solid particles to pass smoothly and for soft energy conversion. At the same time, load distribution along the profile line on the long-screw centrifugal blade is an important factor affecting the energy conversion efficiency of the impeller. Originality/value: The quantitative analysis method of energy in the screw centrifugal pump can help the pump designer improve certain features of the pump and shorten the research cycle.